P083 Method for continuous multichannel measurement of impedance at the auricular sites innervated by various cranial nerves. Issue 3 (March 2017) - Usichenko, T.; Gogola, D.; Dermek, T.; Teplan, M.
Abstract : Question: External auricule receives afferent supply via vagal, trigeminal and cervical nerves (Peuker and Filler, 2002 ). Reduced impedance of the auricular sites innervated by vagal and trigeminal nerves is associated with pain and malfunction of internal organs (Oleson et al., 1980 ;Saku et al., 1993 ). The aim was to develop the robust method for continuous measurement of skin impedance at the sites of auricle, supplied by various cranial nerves. Methods: Multichannel device for continuous impedance measurement, based on Atmel ATmega16 microprocessor with 1 kHz of probing alternating current frequency was controlled using Matlab environment via USB port. The device measures voltage difference between the reference electrode (right forearm) and the sites of interest (innervation areas of cranial nerves) and transforms the voltage values into impedance using the calibration measurements of known resistances. Surface ECG and stainless steel needle electrodes were used at the sites of interest on the right auricles of healthy volunteers. Impedance monitoring was performed at rest and under the heat pain stimuli, delivered via CHEPS thermode (MEDOC analyser, Israel). Results: Reproducible stable data with the voltage of 1 V, current values of 100 μ A and impedance around 10 k Ω were acquired (Fig. 1 ), whereas invasive measurement yielded less variable data than non- invasive procedure. Heat pain stimulation led to differential reduction of the impedance in the sites of cranial nerve innervation (Fig. 2), whereas the decreased impedance recovered to the baseline values (Fig. 2 ). Conclusions: The multichannel continuous measurement of impedance at the external auricle was feasible. Further investigations are warranted to clarify the differential impedance response from the auricular sites in healthy subjects under stress challenge and patients.